Hyperelatosides A–E, biphenyl ether glycosides from Hypericum elatoides, with neurotrophic activity. Issue 47 (25th July 2018) - Yan, Xi-Tao; An, Zhen; Tang, Dan; Peng, Guang-Rui; Cao, Chen-Yu; Xu, Yuan-Zhen; Li, Chun-Huan; Liu, Pei-Liang; Jiang, Zai-Min; Gao, Jin-Ming
Abstract : Five new biphenyl ether glycosides, hyperelatosides A–E, one new benzoate glycoside, hyperelatoside F, were isolated from Hypericum elatoides . Hyperelatosides A, B, and D–F significantly enhanced NGF-induced neurite outgrowth in PC12 cells. Abstract : Five new biphenyl ether glycosides, hyperelatosides A–E (1–5 ), one new benzoate glycoside, hyperelatoside F (6 ), along with nine known phenolic compounds (7–15 ), were isolated from the aerial parts of Hypericum elatoides . Their structures were elucidated by 1D and 2D NMR spectroscopy and HRESIMS, as well as chemical derivatization. This is the first report of the identification of biphenyl ether glycosides as plant metabolites and their possible biosynthetic pathway is proposed. Except for3, the new phenolic metabolites exhibited significant neurotrophic activities to enhance nerve growth factor-induced neurite outgrowth in PC12 cells. In addition, the anti-neuroinflammatory and antioxidant activities of compounds1–15 were preliminarily evaluated in vitro .